Study on Structure Review of Emptying Bottom Outletfor Raising Water Retaining Level of Goupitan Arch Dam - WEI Wei; XIA Chuanxing; ZHU Xi; XIONG Kun (Renmin Zhujiang)
During the normal operation of Goupitan Reservoir, the emptying bottom outlet is blockedby the inlet water retaining gate, or by the working gate at the outlet of the bottom outlet ifthe water retaining gate needs to be repaired. The designed water retaining level of the workinggate and gate support structure is 590 m of dead water level. However, the reservoir actuallyruns above the dead water level for a long time. In order to reduce the waste water during themaintenance of the water retaining gate, the feasibility of raising the water retaining level byworking gate of the bottom outlet needs to be studied. Based on the material mechanics method andthe three-dimensional finite element method, this paper reviews and studies the working gate, gatesupport structure, and bottom outlet structure respectively. Through calculation, it can be knownthat the emptying bottom outlet of the Goupitan arch dam can block the water under 595 m levelsafely, with certain margin.